Adding large woody material into a headwater stream has immediate benefits for macroinvertebrate community structure and function. Issue 4 (25th January 2021) - Al‐Zankana, Ahmed; Matheson, Tom; Harper, David
Abstract: Hydromorphological rehabilitation through installing large woody material (LWM) is increasingly being used to reverse degradation of stream ecosystems. There have been many criticisms of stream rehabilitation projects, because many have not met their goals and many others have not been monitored well enough to assess whether their goals were met. In a before–after–control design (with samples collected 1 year before and two successive years after LWM installation), instream biotopes and their macroinvertebrate assemblages were used as structural and functional units to assess the effectiveness of LWM installed at the Rolleston Brook, a headwater tributary of the River Welland in Leicestershire, UK. The project was successful in enhancing the coefficient of variation of channel water depth and width, wetted surface area, number of instream biotopes, and the biotope diversity in the rehabilitated reach. LWM installation led to significant increases in macroinvertebrate total density, total biomass, and taxon richness. Macroinvertebrate community composition was also enhanced, so that it became more similar to that of the control reach. Small increases in the number of instream biotopes (appearance of gravel and leaf litter) and changes in biotope proportions (decreasing percentage of silt) were significantly related to changes in the macroinvertebrate community metrics in the rehabilitated reach. The results show that using macroinvertebrate community composition is more effective than only using taxon richness and/or diversity metrics for understanding the relationship between LWM installation and macroinvertebrate community responses. To be effective, samples must also be collected in a predefined sampling protocol stratified at the instream biotope level. This approach would be of great benefit in evaluating biodiversity conservation value, and could be incorporated into the advice provided by Natural England concerning restoration and protection of English rivers that are designated as Sites of Special Scientific Interest under UK legislation or Special Areas of Conservation under European legislation.